Dual and selective inhibitors of pteridine reductase 1 (PTR1) and dihydrofolate reductase-thymidylate synthase (DHFR-TS) from Leishmania chagasi - Bárbara Velame Ferreira Teixeira; André Lacerda Braga Teles; Suellen Gonçalves da Silva; Camila Carane Bitencourt Brito; Humberto Fonseca de Freitas; Acássia Benjamim Leal Pires; Thamires Quadros Froes; Marcelo Santos Castilho (Taylor & Francis Group, 2019)
Leishmaniasis is a tropical disease found in more than 90 countries. The drugs available to treat this disease have nonspecific action and high toxicity. In order to develop novel therapeutic alternatives to fight this ailment, pteridine reductase 1 (PTR1) and dihydrofolate reductase-thymidylate synthase (DHF-TS) have been targeted, once Leishmania is auxotrophic for folates. Although PTR1 and DHFR-TS from other protozoan parasites have been studied, their homologs in Leishmania chagasi have been poorly characterized. Hence, this work describes the optimal conditions to express the recombinant LcPTR1 and LcDHFR-TS enzymes, as well as balanced assay conditions for screening. Last but not the least, we show that 2,4 diaminopyrimidine derivatives are low-micromolar competitive inhibitors of both enzymes (LcPTR1 Ki = 1.50-2.30 µM and LcDHFR Ki = 0.28-3.00 µM) with poor selectivity index. On the other hand, compound 5 (2,4-diaminoquinazoline derivative) is a selective LcPTR1 inhibitor (Ki = 0.47 µM, selectivity index = 20).